2016
DOI: 10.3390/ijerph13070718
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Injuries in Singapore: Can Local Physicians and the Healthcare System Do More to Confront This Public Health Concern?

Abstract: Childhood injury is one of the leading causes of death globally. Singapore is no exception to this tragic fact, with childhood injuries accounting up to 37% of Emergency Department visits. Hence, it is important to understand the epidemiology and risk factors of childhood injuries locally. A search for relevant articles published from 1996–2016 was performed on PubMed, Cochrane Library and Google Scholar using keywords relating to childhood injury in Singapore. The epidemiology, mechanisms of injury, risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In studies involving pediatric patients, it has been reported that most of the patients are male and that the severity of trauma increases with the advancing age. [16,17] Ong et al [18] have attributed this to high-risk behaviors that are common in male children. Compatible with the literature, we found that the number of male children with TBI was higher, the age of these patients was higher than others, and the incidence of TBI was higher in boys in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In studies involving pediatric patients, it has been reported that most of the patients are male and that the severity of trauma increases with the advancing age. [16,17] Ong et al [18] have attributed this to high-risk behaviors that are common in male children. Compatible with the literature, we found that the number of male children with TBI was higher, the age of these patients was higher than others, and the incidence of TBI was higher in boys in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective way to prevent falls at home is through structural home modifications (e.g. eliminating steps, covering the floor with non-slip material, installing handrails on stairs, and enclosed balconies) [51,52]. According to a study in New Zealand by Keall M. et al (2015) [53], the average cost of securing a home to prevent falls is around 830 dollars (USD).…”
Section: Falls In the Home Environmentmentioning
confidence: 99%
“…Approximately 80% (3.9 million) of the 5 million deaths caused by injuries each year (or injuries) are unintentional injuries 2 .Injuries were the cause of 364,824 children deaths in 2015, according to the most recent World Health Organization (WHO) data source 3 .Children under the age of 5 experience the majority of unintentional injuries in and around the house, where they spend the majority of their time 4 .…”
Section: Introductionmentioning
confidence: 99%